Análise da estrutura de capital de empresas brasileiras de capital aberto (2003-2012): uma nova verificação da Static Trade-off e da Pecking Order - Maria Elisa Lima Pereira (2013)
The present work has as its goal a new verification of two theories: the Static Trade-off Theory and the Pecking Order Theory about the structure of capital in Brazilian companies, by means of the tests developed by Rajan and Zingales (1995) and Shyam-Sunder and Myers (1999). Our group of samples comprises 132 non-financial Brazilian companies, listed in the BM&FBOVESPA in the period that spans from 2003 to 2012. In this study, we have employed the regression model with panel data. The results of the Rajan and Zingales (1995) model, in the analysis of the set of samples, indicated that there is a stronger adherence to the STT, as well as a difference between sub-periods. In the period ranging from 2003 to 2007 there has occurred a stronger adherence to the STT, while on the period that goes from 2008 to 2012 the result has not proven conclusive towards either one of the theories. Furthermore, the yearly dummy variables have proven more significant from 2008 to 2012, indicating thereby that the macroeconomic impacts that took place in this period, especially the effects of the Subprime crisis, had great influence over the financing decisions of companies. Through the classifications of companies according to active growth, profit, and size, it is possible to observe the difference between the determining factors and their significance in explaining the companies´ levels of debt. The ones with higher profits have shown stronger adherence to the STT in both periods. From 2003 to 2007, all sub-samples corroborated the STT. And, in the following period, from 2008 to 2012, the results have not proven conclusive towards either theory for the majority of sub-samples. Moreover, the medium-sized businesses and negative profits presented results favorable to the POT. That result agrees with Fama and French´s (2005) idea and with the study by Iquiapaza, Amaral and Araújo (2008),both of wich note that there is weak evidence to corroborate the POT.